PELATIHAN CANVA: PENGEMBANGAN KETERAMPILAN DIGITAL UNTUK SISWI SMA SANTA MARIA YOGYAKARTA - Dharomesz, Vonezyo Yupanzara; Pratama, Yohanes Mario; Aji, Mario Rosario Wisnu; Mayasari, Agatha; Pramusiwi, Aloysia Desy; Adyantari, Api; Pradana, Bartolomeus Galih Visnhu; Budiyono, Elizabeth Fiesta Clara Shinta; Sasmita, Raymundo Patria Hayu; Putra, Tegar Satya (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Starting with understanding the importance of technological skills in the modern workplace, this community service targets Santa Maria High School Yogyakarta students to gain better knowledge and skills in using Canva to make presentations and create the curriculum vitae. Focuses on transferring knowledge and technical skills and aims to improve students' critical thinking and problem-solving abilities. Students are encouraged to develop their creativity and think outside the box when presenting information and completing specific tasks and preparing to enter the workforce or continue their studies at a higher education level. It directly benefits students' technological skills and has a significant long-term impact, with increased hard skills in Canva and honed problem-solving abilities. This community service contributes positively to strengthening the relationship between schools and the world of work by ensuring that high school graduates have skills relevant to current industry needs.